Dynamic changes and metabolic function of intestinal flora in patients with postoperative pneumonia after lung cancer surgery - Meiling Wang; Weiting Jiang; Tingyu Wei; Zimeng Li; Yaxin Jiang; Pengcheng Zhou; Bizhen Chen (PLoS ONE, 2025)
Background Postoperative pneumonia (POP) is the most prevalent postoperative complication following lung cancer surgery. It is a crucial factor that influences surgical success and the rapid recovery of patients. Studies on the gut-lung axis have suggested that changes in the structural and functional aspects of intestinal flora are implicated in the incidents and development of pulmonary infection. This study aims to reveal the dynamic changes and metabolic function of intestinal flora in lung cancer patients with POP, with the ultimate goal of providing novel insights and targets for the prevention and treatment of POP. Methods This study includes three groups: healthy control group, lung cancer with POP group, and lung cancer without POP group. We collected stool samples from healthy individuals, preoperative and first post-infection stool samples from the POP group, and preoperative and first postoperative stool samples from the non-POP group. The hypervariable V3-V4 regions of 16S rRNA gene were sequenced using Illumina MiSeq high-throughput sequencing technology. Results The alpha diversity index was lower in the POP group than in the healthy group, the beta diversity index was also different between the two groups (P <  0.05). Eggerthella, Coprobacillus, and Peptostreptococcus were abundant in the intestinal tracts of the POP group in preoperative and postoperative infections. There was a decrease in the abundance of beneficial genera such as Blautia and an increase in the abundance of pathogenic or opportunistic pathogens such as Bacteroides. The phosphatidylinositol signaling system abundance increased, whereas the abundance of phenazine, phenylalanine, tyrosine, and tryptophan biosyntheses was reduced in the POP group during postoperative infection. Conclusion Patients with POP after lung cancer surgery have a distinct spectrum of intestinal flora. The intestinal flora displays a reduction in diversity and an increase in the presence of potential pathogenic bacteria, which impact metabolic functions.